Evolução ponderal, glicêmica e lipídica em mulheres obesas submetidas à cirurgia bariátrica: seguimento de 12 meses - Sgarioni, Augusto Cardoso (My University, 2022)
The global epidemic of obesity contributes, substantially, to the high prevalence of cardiometabolic diseases. Both sexes are affected, however, recent data shows that the prevalence in the female population is greater than in males. Differences are also present in the pathophysiology, evolution, and related comorbidities, due to genetic, biological, and psychosocial features, peculiar to each sex. In addition, a greater proportion of women seek surgical treatment after failure with other types of interventions. Bariatric and metabolic surgery have been highlighted and improved over time, especially due to the significant increase in severe obesity in the population. Furthermore, it is known that approximately 80% of obese people who undergo this type of surgery are women. This reality also occurs at the reference service in bariatric and metabolic surgery in the southeastern region in the state of Rio Grande do Sul, Brazil. Therefore, this study evaluated the weight, glycemic, and lipid levels during 12 months of surgical treatment for obesity in the population of women. This was a retrospective cohort study, with data collected from women with severe obesity who underwent bariatric and metabolic surgery using the Roux-en-Y gastric bypass (RYGB) technique in the period between 2017 to 2020. It is noteworthy that the present study was carried out with the population of a public service which is a reference in bariatric and metabolic surgery. The body mass index (BMI), fasting blood glucose, glycated hemoglobin (HbA1c), total cholesterol, HDL-cholesterol, LDL-cholesterol, and triglycerides (TG) were evaluated in five- time frames (T): preoperative evaluation (T1); 30 days of postoperative (PO) (T2); 3 months of PO (T3); 6 months of PO (T4); and 12 months PO (T5). One hundred and fifty women were included, with an average age of 43.69±9.87; BMI of 45.4 ± 5.4, arterial hypertension (79.3%), type 2 diabetes (38%), and dyslipidemia (30.7%). No deaths occurred in the PO. In the period of follow-up, BMI showed a statistically significant reduction (p<0.001) at all times analyzed. The loss of BMI excess was 68.2%. In the comparison T1 vs T5, there was a significant reduction in blood glucose (p<0.01), HbA1c (p<0.01), CT (p<0.001), LDL-c (p<0.01) and TG (p<0.01). HDL-c showed an increase in the period, however, without a statistical difference (p=0.3). At the end of the study, 86%, 87% and 72% of the population were no longer using medication for DM2, dyslipidemia, and arterial hypertension, respectively. It was concluded that in this female population with severe obesity undergoing bariatric and metabolic surgery, there were significant short-term improvements in metabolic health. Furthermore, RYGB proved to be an effective treatment in the remission of comorbidities. [resumo fornecido pelo autor]
A epidemia global de obesidade contribui, substancialmente, para as altas prevalências de doenças cardiometabólicas. Ambos os sexos são atingidos, entretanto, dados recentes mostram que a prevalência na população de mulheres é maior do que em homens. Diferenças também estão presentes na fisiopatologia, evolução e comorbidades relacionadas, devido a características genéticas, biológicas e psicossociais, peculiares a cada sexo. Além disso, maior proporção de mulheres busca o tratamento cirúrgico após insucesso com outros tipos de intervenções. A cirurgia bariátrica e metabólica tem sido destacada e aprimorada ao longo do tempo, especialmente com o significativo aumento de obesidade grave na população. Ademais, sabe-se que cerca de 80% dos obesos submetidos a esse tipo de cirurgia são mulheres. Essa realidade também ocorre no serviço de referência em cirurgia bariátrica e metabólica da região sudeste do Rio Grande do Sul. Por isso, este estudo avaliou a evolução ponderal, glicêmica e lipídica durante 12 meses do tratamento cirúrgico para obesidade na população de mulheres. Tratou-se de um estudo de coorte retrospectivo, com dados de mulheres com obesidade grave submetidas à cirurgia pela técnica de gastroplastia com derivação intestinal em ?Y? de Roux (GYR) no período de 2017 a 2020. Destaca-se que o presente estudo foi realizado com a população de um serviço público de referência em cirurgia bariátrica e metabólica. O índice de massa corpórea (IMC), glicemia de jejum, hemoglobina glicada (HbA1c), colesterol total, HDL-colesterol, LDL-colesterol e triglicérides (TG) foram avaliados em cinco tempos (T): avaliação pré-operatória (T1); 30 dias do pós-operatório (PO) (T2); 3 meses de PO (T3); 6 meses de PO (T4); e 12 meses PO (T5). Cento e cinquenta mulheres foram incluídas, com idade média de 43,69±9,87; IMC de 45,4 ± 5,4, hipertensão arterial (79,3%), diabetes tipo 2 (38%) e dislipidemia (30,7%). Nenhum óbito ocorreu no PO. No período do seguimento, o IMC apresentou redução estatisticamente significante (p<0,001) em todos os tempos analisados. A perda de excesso de IMC foi de 68,2%. Na comparação T1 vs T5 ocorreu redução significante da glicemia (p<0,01), HbA1c (p<0,01), CT (p<0,001), LDL-c (p<0,01) e TG (p<0,01). O HDL-c mostrou aumento no período, porém, sem diferença estatística (p=0,3). Ao final do estudo, 86%, 87% e 72% da população não estava mais usando medicamentos para DM2, dislipidemia e hipertensão arterial, respectivamente. Concluiu-se que nessa população de mulheres com obesidade grave e submetidas à cirurgia bariátrica e metabólica ocorreu melhorias significativas, em curto prazo, na saúde metabólica. Ademais, a GYR mostrou-se como um tratamento eficaz na remissão de comorbidades. [resumo fornecido pelo autor]
Keywords: Obesidade - Mulheres; Cirurgia bariátrica; Obesity - Woman; Obesity - Surgery